A novel way of Subfoveal Perfluorocarbon liquid Removal using 26 gauge spinal anesthesia needle - Anand, Abhishek; Agarwal, Lalit; Agrawal, Nisha (Nepalese Journal of Ophthalmology, 2020)
Introduction: Perfurocarbon Liquid (PFCL) is an essential adjunct of retinal detachment surgery. Subfoveal migration of PFCL is a rare and vision threatening complication of its use. Various techniques have been described for its removal. However, no consensus on ideal technique of its removal has been established. We present a novel, relatively atraumatic and cost effective way of PFCL removal using a widely available 26Ga spinal anesthesia needle. Case: An 18 years old myopic patient who had undergone left eye pars plana vitrectomy (PPV) for myopic Rhegmatogenous Retinal Detatchment (RRD) in the past presented after 1 month with retained subfoveal PFCL. Its subretinal location was confirmed by Optical Coherence Tomography (OCT). He was taken up for early Silicone Oil Removal (SOR) along with removal of retained subfoveal PFCL under high magnification by using a surgical disposable contact macula lens. A 26G spinal anesthesia needle tip was used to dissect a small separation parallel to the nerve fibers at the temporal edge of tense cystic PFCL bleb. Silicone tipped flute cannula was used to passively aspirate the sub retinal PFCL under fluid with no additional intervention. No barrage LASER was done. Observation: Anatomical restoration of the retina was noted both intraoperatively and post-operatively. SD-OCT showed complete restoration of anatomical layers with no presence of intraretinal cystic cleft both at day 1 and 30 days postoperatively. Conclusion: Safe removal of subfoveal PFCL can be done with 26Ga spinal anesthesia needle which is atraumatic, inexpensive and readily available. However, long term validity of this process needs to be established in a case series.